Pengembangan Sistem Informasi Akreditasi Program Studi Berbasis Web di Fakultas Teknik Universitas Udayana - Utami, Ni Made Cyntia; Setiawati, Ni Luh Putu Lilis Sinta; Komaladewi, Anak Agung Istri Agung Sri; Setyawan, Ferdiansyah Pratama Putra (LPPM STT Terpadu Nurul Fikri, 2025)
The accreditation process is vital for study programs to gain recognition for their performance. Accreditation applications require supplementary data to support the Program Performance Report (LKPS) and develop the Self-Evaluation Report (LED). At the Faculty of Engineering, Udayana University (FT Unud), data collection is still conducted manually, leading to inefficiencies. This study aims to develop SIAP 4.0, a web-based accreditation support system for study programs at FT Unud, adhering to Decree No. 186/M/2021 issued by Kepmendikbudristek. Using the Waterfall methodology, the system was designed through stages including requirements definition, analysis, design, coding, testing, and maintenance. The system was built with the PHP Laravel framework, HTML, jQuery, and MySQL, and deployed on the Amazon Web Service EC2 Instance server. To ensure data security, user access to SIAP 4.0 is managed through registration and admin authorization. The system offers three core features: data input, visualization, and export, simplifying centralized and up-to-date data management. These functionalities enable efficient addition, editing, and deletion of accreditation data, improving the overall accreditation process at FT Unud.